2019
DOI: 10.3847/1538-4357/aaf727
|View full text |Cite
|
Sign up to set email alerts
|

Height Dependence of the Penumbral Fine-scale Structure in the Inner Solar Atmosphere

Abstract: We studied the physical parameters of the penumbra in a large and fully-developed sunspot, one of the largest over the last two solar cycles, by using full-Stokes measurements taken at the photospheric Fe I 617.3 nm and chromospheric Ca II 854.2 nm lines with the Interferometric Bidimensional Spectrometer. Inverting measurements with the NICOLE code, we obtained the three-dimensional structure of the magnetic field in the penumbra from the bottom of the photosphere up to the middle chromosphere. We analyzed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…In this regard, it must be noted that such a configuration is reminiscent of the two components -spines/intraspines -observed in regular penumbrae: the horizontal component, which is referred to as intra-spines, or fluxtube component, that carries the Evershed flow, and other more vertical component, spines or background component, with stronger magnetic field intensity. Such a fluted or "uncombed" structure of the penumbral magnetic fields on small scales along the azimuthal direction was recognized in observations by Lites et al (1993); Solanki & Montavon (1993); Title et al (1993) and later confirmed by a number of investigations with increasing spatial and spectral resolution (Martínez Pillet 2000;Schlichenmaier & Collados 2002;Bellot Rubio et al 2004;more recently, Tiwari et al 2015 andMurabito et al 2019, who found such a fine structure also at the chromospheric level).…”
Section: Discussionmentioning
confidence: 78%
“…In this regard, it must be noted that such a configuration is reminiscent of the two components -spines/intraspines -observed in regular penumbrae: the horizontal component, which is referred to as intra-spines, or fluxtube component, that carries the Evershed flow, and other more vertical component, spines or background component, with stronger magnetic field intensity. Such a fluted or "uncombed" structure of the penumbral magnetic fields on small scales along the azimuthal direction was recognized in observations by Lites et al (1993); Solanki & Montavon (1993); Title et al (1993) and later confirmed by a number of investigations with increasing spatial and spectral resolution (Martínez Pillet 2000;Schlichenmaier & Collados 2002;Bellot Rubio et al 2004;more recently, Tiwari et al 2015 andMurabito et al 2019, who found such a fine structure also at the chromospheric level).…”
Section: Discussionmentioning
confidence: 78%
“…Such a difference can introduce an additional phase term in the case of a propagating wave. The problem of the determination of the height of formation of the intensity and magnetic signals in the Ca 854.2 nm spectral line was addressed in great detail in Murabito et al [61], Cauzzi et al [70], Quintero Noda et al [71]. In addition, the height difference can also dynamically change in a magneto-hydrodynamic atmosphere, a circumstance that may also contribute to the width of the distribution of the phase measurements seen in figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to radiometric calibration, polarimetric demodulation and cross-talk minimization between the Stokes parameters was included in the calibration process. This dataset was also studied in Stangalini et al [60], Murabito et al [61], Houston et al [62], Murabito et al [63] In order to ensure the reliability of the results, here we restrict our attention to the intensity and CP fluctuations only. This choice is also motivated by the fact that since the Ca II 854.2 nm spectral line often goes into emission, the estimation of the Doppler velocity may lead to inconsistencies [64].…”
Section: Methodsmentioning
confidence: 99%
“…Both the SDO /HMI and IBIS photospheric observations show that the penumbra of AR was formed by bright filaments and dark spines nearly radially aligned over most of the sunspot structure (Murabito et al 2019), except for an area close to the EFRs observed on 2016 May 20. Figure 1 shows the region analyzed in our study as deduced from SDO /HMI continuum observation performed on 2016 May 19 at 13:34 UT and the region of interest (ROI) discussed in the following and shown in Starting from 2016 May 19 12:00 UT the ROI showed in about 24 hours an increase of the LOS magnetic flux of about 2 − 4 × 10 20 Mx for the positive and negative polarity, and a flux decrease afterwards.…”
Section: Analysis and Resultsmentioning
confidence: 96%
“…The data were processed with the methods described by, e.g., Ermolli et al (2017). The same dataset was also analyzed by Stangalini et al (2018) and Murabito et al (2019), which we refer to the reader for further details.…”
Section: Observationsmentioning
confidence: 99%